Hyperthyroid Status with Glycemic Control in Patients with type 2 Diabetes Mellitus at Peripheral Hospital - Nahak, Jolanda; Julency (Lombok Medical Journal, 2025)
By 2030, it is estimated that the number of patients with type 2 diabetes mellitus (T2DM) in Indonesia will increase from 8.4 million to 21.3 million. Thyroid dysfunction (TD) has an impact on the glycemic control of patients with T2DM. This case report explores a case of a T2DM patient, with hyperthyroidism and glycemic control in a peripheral hospital, including Pre Hospital, Intra Hospital, and Post Hospital status. In this case, a 25-year-old woman presented with typical thyroid symptoms accompanied by a significant increase in blood glucose, the patient was carried out strict glycemic control in the ward, although no treatment was carried out in the intensive care unit (ICU) due to limited facilities, but on the fourth day of treatment the patient's clinical condition improved and blood glucose level was controlled. In our report, in pre-, intra, and post-hospital, type 2 DM patients with hyperthyroid status, following glycemic control before, during, and after hospitalization, we found that routine blood glucose levels monitoring had a positive impact on the patient's clinical condition in these 3 time periods. Therefore, it is essential to screen for TD in T2DM patients as each of the high cardiovascular risks in patients with diabetes mellitus and thyroid.